ChemInform Abstract: Direct Catalytic Asymmetric Synthesis of β‐Hydroxy Acids from Malonic Acid. Issue 18 (April 2016) - Gao, Hang; Luo, Zhenli; Ge, Pingjin; He, Junqian; Zhou, Feng; Zheng, Peipei; Jiang, Jun
Abstract: Starting from tryptanthrin and its derivatives, a series of cephalanthrin A analogues is prepared via nickel(II)‐catalyzed asymmetric addition of malonic acid.